Negative Differential Resistance of n-ZnO Nanorods/p-degenerated Diamond Heterojunction at High Temperatures - Sang, Dandan; Liu, Jiaoli; Wang, Xiaofeng; Zhang, Dong; Ke, Feng; Hu, Haiquan; Wang, Wenjun; Zhang, Bingyuan; Li, Hongdong; Liu, Bo; Wang, Qinglin (Frontiers in Chemistry, 2020)
In the present study, a n-ZnO nanorods (NRs)/p-degenerated diamond tunneling diode was investigated with regards to its temperature-dependent negative differential resistance (NDR) properties and carrier tunneling injection behaviors. The fabricated heterojunction demonstrated NDR phenomena at 20 and 80 oC. However, these effects were disappeared followed by the occurrence of rectification characteristics at 120 oC. At higher temperatures, the forward current was increased, while the turn-on voltage and peak-to-valley current ratio (PVCR) were reduced. Besides, the underlying mechanisms of carrier tunneling conduction at different temperature and bias voltages were analyzed through the schematic energy band diagrams and semiconductor theoretical models. High-temperature NDR properties of n-ZnO NRs/p-degenerated diamond heterojunction can extend the applications of resistive switching and resonant tunneling diode, especially in high-temperature and high-power environments.